Application Analysis of MMC-HVDC AC Tie Line Transmission in New Energy Power Generation. (28th September 2022) - Sun, Ruijuan; Dang, Xiaoyuan; Yang, Jiayi
Abstract : In order to solve the problem of new energy power generation, the author proposes an application analysis method based on MMC-HVDC AC tie line transmission in new energy power generation. This method analyzes the research status of the operation, protection, and control of HVDC flexible transmission systems in various countries and summarizes the advantages of flexible HVDC transmission systems compared with traditional DC, the research focus of the system protection control is explored from the research methods and research ideas. Experimental results show that: the dynamic response of the average value of the capacitor voltage when the two control systems are subjected to external disturbances, the disturbance is set as the DC side voltage rise, and the amplitude is 5%. Conclusion . MMC-HVDC is beneficial to improve the stability and reliability of system operation.